26 Post discharge follow-up for patients infected or colonized with multidrug-resistant organisms. (25th October 2019) - Taguas, Roxanne Mora; ,; Mohideen, Allan; Tana, Juinarah; Deyab, Elma Lou; Qudsi, Ola; Yaseen, Areej; AlAhmadi, Muhammad; Saedi, Maher Al; ,
Abstract : Background: The spread of multidrug-resistant organisms (MDROs) among admitted patients is one of the major threats facing many hospitals in Saudi Arabia. These organisms include methicillin-resistant Staphylococcus aureus (MRSA), vancomycin- resistant enterococci (VRE), and certain gram-negative bacilli (GNB). There have been increasing challenges in providing and fully implementing specific infection control strategies for affected patients during their hospital stay. Current hospital infection control guidelines recommend single rooms for every MDRO colonized or infected patient. This should be continued while patients are in hospital and upon readmission unless patients are successfully cleared. Evidence of clearance from MDRO colonization is needed before patients are considered non-infectious. Although clearance of MDRO infected and colonized patients is successfully carried out during hospital stay, a major lack of such activity has been identified after patients are discharged from hospitals. The purpose of tracing patients post discharge is to ensure that they will be screened and re-swabbed during their outpatient appointments to assess whether they no longer require extra infection control measures, such as isolation precautions, during their subsequent admission, thereby reducing the need for single rooms. Methods: All patients discharged with MDROs were tracked by the assigned infection control practitioner (ICP). The ICP tracked the appointments of these patients. Notification and instruction for swabbing and rescreening were delivered to responsible nurses at the outpatient department (OPD) using the OPD notification forms. Results: Of 271 discharged patients with MDRO infection or colonization, 38 (14%) patients were successfully cleared and deflagged from MDROs; 40 (14.7%) were not given an OPD appointment; 19 (7%) were not swabbed; 61 (22.5%) have no doctor's order; 34 (12.5%) were readmitted; 10 (3.6%) were swabbed but still yielded positive results; 11 (4%) were given very long appointment; and 9 (3%) were transferred to another facility and/or home healthcare. Conclusion: This exercise proved to be very tasking for any ICP to undertake. In addition, multiple challenges have been identified which require administrative support, commitment, and participation of all healthcare workers to decrease demand on isolation beds and to reduce risk of MDRO transmission.